Schwannoma: An uncommon dweller in the adrenal gland - Chaithra G Venkataramana; Saraswathy Sreeram; P V Santosh Rai; G G Laxman Prabhu; K N Sanman; Shrinath P Shetty (Wolters Kluwer Medknow Publications, 2020)
An elderly adult woman presented with upper abdominal pain to the urology department. Imaging studies revealed a right adrenal lesion with central necrosis, abutting the large vessels and suggestive of malignancy. Histopathology showed an encapsulated spindle cell tumor with marked nuclear atypia, cystic change, and hemorrhage. S100 immunomarker was strongly and diffusely positive. Final diagnosis was ancient schwannoma with secondary change. Schwannomas are rare in the adrenal gland, with <50 cases reported in the literature. These incidentally detected nonfunctional adrenal tumors need confirmation with histopathology and ancillary studies.